UAV Communications and Networks - Park, Soohyun; Lee, Ju Hyung; Jung, Soyi; Kim, Joongheon (Signals and Communication Technology, 2024)
Witnessing the recent developments of UAV-assisted networks, such as Loon by Loon LLC, Aquila by Facebook, and HAWK30 by HAPSMobile, we are at the cusp of a communication revolution where non-terrestrial networks (NTN) are envisaged to meet the terrestrial networks through the sky. Wireless connectivity has already been extending towards the sky by integrating unmanned aerial vehicles (UAVs). UAV-assisted communication can efficiently secure and utilize the favorable channel condition, thanks to its flexible maneuverability. The application of such mobile platform is not limited to supporting existing network infrastructure (i.e., data offloading), disaster management, data collection for IoT, and so on. However, to fully utilize such a flexible but energy-limited UAV platform, there are many considerations and challenging issues, which will be elucidated throughout this chapter.
Keywords: Aerial vehicle; Autonomous mobilities; Charging; Resources allocation; Surveillance; Terrestrial networks; Trajectory optimization; Unmanned aerial vehicle; Vehicle communications; Vehicle network; Autonomous mobility; Charging; Resource allocation; Surveillance; Trajectory optimization; UAV